Perspectives in dryland restoration: approaches for climate change adaptation - Ramón Vallejo, V.; Smanis, Athanasios; Chirino, Esteban; Ramo, V.; Fuentes, David; Valdecantos, Alejandro; Vilagrosa, Alberto (New Forests, 2012)
Reforestation efforts in dryland ecosystems frequently encounter drought and limited soil productivity, although both factors usually interact synergistically to worsen water stress for outplanted seedlings. Land degradation in drylands (e.g. desertiﬁcation) usually reduces soil productivity and, especially, soil water availability. In dry sub-humid regions, forest ﬁres constitute a major disturbance affecting ecosystem dynamics and reforestation planning. Climate change projections indicate an increase of drought and more severe ﬁre regime in many dryland regions of the world. In this context, the main target of plantation technology development is to overcome transplant shock and likely adverse periods, and in drylands this is mostly related to water limitations. In this paper, we discuss some selected steps that we consider critical for improving success in outplanting woody plants, both under current and projected climate change conditions including: (1) Plant species selection, (2) Improved nursery techniques, and (3) Improved planting techniques. The number of plant species used in reforestation is increasing rapidly, moving from a reduced set of well-known, easy-to-grow, widely used species, to a large variety of promising native species. Available technologies allow for reintroducing native plants and recovering critical ecosystem functions for many degraded drylands. However, climate change projections introduce large uncertainties about the sustainability of current reforestation practices. To cope with these uncertainties, adaptive restoration approaches are suggested, on the basis of improved plant quality, improved techniques for optimizing rain use efﬁciency in plantations, and exploring native plant species, including provenances and genotypes, for their resilience to ﬁre and water use efﬁciency.
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: Mediterranean ecosystems; Nursery cultivation; Reforestation; Species selection; Water harvesting